Spatial and economic assessment of agropolitan zones with focus on rice and coconut: Implications for sustainable agricultural development - Prakusya, Yudya Alif Ridhoni (Journal of Agrosociology and Sustainability, 2025)
Background: Banyumas Regency is one of the districts that has good potential in the agricultural sector. Banyumas Regency itself since 2011 has been developing the Agropolitan Area listed in the RTRW of Banyumas Regency. However, in reality this policy has not been able to work, both systemically and spatially. Therefore, this study tries to assess how the development of the Banyumas Regency Agropolitan Area will be in the future. Methods: By using two commodity bases namely rice and coconut to be developed, this study assesses which locations are suitable for farming areas, production centers, as well as markets and urban centers in the Agropolitan Area of Banyumas Regency. By analyzing the suitability of the village location, namely the suitability of land for farming areas and a composite index with a z score, it can be determined which areas are suitable for the development of the Banyumas Regency Agropolitan Area. By also looking at the characteristics and accessibility, it is also assessed how the connectivity between functional areas in the Agropolitan Area of Banyumas Regency is assessed. Findings: The findings indicate that the entire Agropolitan Area in Banyumas is suitable for rice and coconut cultivation, with 11 villages identified as optimal locations for production centers and four villages deemed highly suitable for market and urban areas. Conclusion: This study conclude that rice and coconut have good land suitability in the Agropolitan Area of Banyumas Regency, with six villages unsuitable for farming and four villages unsuitable for coconut cultivation. Novelty/Originality of this article: This research contributes novel insights into spatial planning and economic development by integrating commodity-based land suitability with accessibility analysis, providing a strategic framework for sustainable agricultural development in Banyumas Regency.